Cognitive adaptations to criminal justice lead to "paranoid" norm obedience. (April 2017) - Patrzyk, Piotr M.; Takáč, Martin
People often cooperate and obey norms in situations where it is clear they cannot be caught and punished. Such behavior does not serve their self-interest, as they are foregoing opportunities to exploit others without any negative consequences. Hence, it is not clear how this behavior could have evolved. Some previous explanations invoked the existence of other-regarding preferences, moral motivation, or intrinsic concern for social norms. In this study, we develop an agent-based model illustrating that none of these is necessary for the emergence of norm-abiding behavior. Our model suggests evolutionary pressure against norm violators may lead to the emergence of a bias, causing agents to be extremely sensitive to the probability of being caught. Because of this, they often incorrectly classify anonymous situations as non-anonymous ones and obey social norms due to the fear of being punished. In our simulations, we show that cooperation is promoted by (1) the number of interactions actually observed, (2) the strength of punishments against norm violators, and most importantly, (3) the uncertainty in agent classifications.